Using Reading Comprehension Strategies to enhance Students' Reading Proficiency in Nigerian Secondary Schools - Akubo, Esther (NIU Journal of Humanities, 2019)
Reading is an active developmental process in which the reader constructs meaning by using information from the text as well as his prior or background knowledge. It is also the ability to make sense of the content of what is read from print. Reading comprehension is a basic tool that enables an individual, particularly students meet the reading demands of their academic discipline. To be able to attain proficiency in one's area of work, one needs reading skills in general and specific knowledge, which keeps one sharp, smart and alert. Researchers have proven that good readers are more productive and efficient than poor readers. Reading is a booster to self- esteem and intelligence and helps one to have firm grips of life and circumstances. It is therefore very imperative for readers particularly students to be strategic in their reading comprehension to enable them attain the level of desired proficiency. This work considered the concepts of reading, causes of poor reading, importance of reading, and reading strategies such as Literary Awareness Program (LAP), News on the Board (NOB), and Language Experience Approach (LEA) at the lower level. At the higher or secondary school level. Strategies such as skimming, scanning, speed reading and a host of others are used to enhance reading comprehension  among Nigerian secondary schools students . Keywords :  Proficiency, Comprehension, Strateg